Prevalence of hepatitis B and hepatitis C in patients of chronic kidney disease - Sehgal, Rishabh; Singh, Harsimranjit; Singh, Inderpal; Mittal, Jyotisterna; Gupta, Payal; Kaur, Kanwerpreet (International Journal of Research in Medical Sciences, 2019)
Background: Patients of CKD are highly exposed to HBV and HCV because of multiple blood transfusions and exposure to contaminated equipments. Infections by HBV and HCV are significant cause of morbidity in CKD patients by causing liver damage and membranoproliferative GN. Present study was done to observe the prevalence of HBV and HCV in patients of CKD and to compare the prevalence of these infections in patients who were on maintenance haemodialysis and who were not on maintenance hemodialysis. Methods: This study had been conducted on 140 patients. Patients were diagnosed as having CKD on basis of Cockcroft-gault equation as per KDOQI guidelines. Stage 3, 4 or 5 patients were included for the study whereas patients with stage 1 or 2 were excluded. These 140 cases were divided into 2 groups, Group I included 70 cases who were on maintenance hemodialysis and Group II included 70 patients who were not on maintenance hemodialysis. The prevalence of HBV and HCV in the two groups was observed. Diagnosis of HBV was made by detection of HBsAg (one step immunoassay) and diagnosis of HCV was made by detection of antibodies to Hepatitis C(enzyme linked immunoassay). Prevalence data of NCDC was used for comparison with general population. Results: In Group I, 15 (21%) patients were positive for HCV and 9 (12.9%) were positive for HBV which is significantly higher compared to Group II patients in which 6 (8.6%) and 2 (2.9%) were positive respectively. Overall out of 140 patients,21(15%) were positive for HCV and 11(7.9%) were positive for HBV, which is significantly higher compared to data of NCDC for general population in which prevalence of HCV and HBV is 1% and 4% respectively Conclusions: Prevalence of HBV and HCV was significantly higher in patients of CKD than the general population, which was further higher in patients who were on maintenance hemodialysis and have received multiple blood transfusions, emphasizing the need to implement the methods to limit the spread of HBV and HCV.